MATERNITY CAPITAL AND THE MOTHERHOOD WAGE PENALTY: EVIDENCE FROM RUSSIA - Kenzhetayev, Rustem (Nazarbayev University School of Sciences and Humanities, 2022)
This paper analyzes the implications of the maternity capital policy on the earnings of mothers with one or two children under 18 in Russia. The main goals of this paper are to obtain the most recent estimates of the motherhood wage penalty in Russia and to observe the impact of the maternity capital policy on the magnitude and the direction of the motherhood wage gap. I use the Fixed-Effects model to control for the individual specific heterogeneity and I utilize propensity score matching to control for the self selection. The results suggest a presence of the motherhood wage gap in the order of 3-4% for one child under 18 and 6-10% for two children under 18 on average. Overall, the maternity capital policy decreased the wage differentials between mothers with two children and non-mothers. However, this decrease was not sufficient to eliminate the motherhood wage penalty or turn it into the motherhood wage premium
Keywords: Type of access: Open Access; maternity capital policy; Russia; motherhood